First Inventory of Sea Anemones (Cnidaria: Actiniaria) of the Mexican Caribbean - Gonzalez-Muñoz, Ricardo; Simões, Nuno; Sanchez-Rodriguez, Judith; Rodriguez, Estefania; Segura-Puertas, Lourdes (Zootaxa, 2012)
Ten species of sea anemones (Anthozoa: Actiniaria) are documented in the Mexican Caribbean based on observations andcollections in 11 coral reef localities during 2006–2011; three of them are new records for Mexico. These species belongto families Actiniidae, Aiptasiidae, Aliciidae, Boloceroididae, Phymanthidae, and Stichodactylidae. Although these do notrepresent all species reported in the Mexican Caribbean, these are the most abundant and conspicuous. This work represents the first inventory of sea anemones of the Mexican Caribbean.